Rapid tranquillisation in a psychiatric emergency hospital in Lebanon: TREC-Lebanon – a pragmatic randomised controlled trial of intramuscular haloperidol and promethazine v. intramuscular haloperidol, promethazine and chlorpromazine. Issue 13 (6th October 2022) - Dib, Joseph E.; Yaacoub, Hiba Edward; Ikdais, Werner Henry; Atallah, Elie; Merheb, Tony Jean; Ajaltouni, Jean; Akkari, Myriam; Mourad, Marc; Nasr, Maria Elias; Hachem, Dory; Kazour, Francois; Tahan, Fouad; et al.
Abstract: Background: Agitated patients constitute 10% of all emergency psychiatric treatment. Management guidelines, the preferred treatment of clinicians differ in opinion and practice. In Lebanon, the use of the triple therapy haloperidol plus promethazine plus chlorpromazine (HPC) is frequently used but no studies involving this combination exists. Method: A pragmatic randomised open trial (September 2018–July 2019) in the Lebanese Psychiatric Hospital of the Cross in Beirut Lebanon involving 100 people requiring urgent intramuscular sedation due to aggressive behaviour were given intramuscular chlorpromazine 100 mg plus haloperidol 5 mg plus promethazine 25 mg (HPC) or intramuscular haloperidol 5 mg plus promethazine 25 mg Results: Primary outcome data were available for 94 (94%) people. People allocated to the haloperidol plus promethazine (HP) group showed no clear difference at 20 min compared with patients allocated to the HPC group [relative risk (RR) 0.84, 95% confidence interval (CI) 0.47–1.50]. Conclusions: Neither intervention consistently impacted the outcome of 'calm', or 'asleep' and had no discernible effect on the use of restraints, use of additional drugs or recurrence. If clinicians are faced with uncertainty on which of the two intervention combinations to use, the simpler HP is much more widely tested and the addition of chlorpromazine adds no clear benefit with a risk of additional adverse effects.